2020
DOI: 10.4028/www.scientific.net/msf.992.652
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation of Composite Wear-Resistant Nickel Ectrodeposits with Nanoparticles

Abstract: The composition of the electrolyte-colloid was optimized by the method of mathematical planning of extreme experiments of Box-Wilson to obtain a composite electrochemical coating of nickel-nanodiamond. Polarization researches have shown a decrease in polarization in electrolytes containing diamond nanoparticles. The effect of the colloidal phase introduced into the electrolyte or formed during the electrolysis process on the electroplating process and the quality of precipitation was discussed. The wear resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…7H2O 8-15; C7H5NO3S 0,5-2,0; ND 0,5-2,5. Electrolysis modes: pH 1,5-5,0; temperature 20-60°C; cathode current density 0,5-43 A/dm 2 ; stirring with a mechanical stirrer at a speed of 80-120 rpm [17]. Kinetic studies [16][17] have shown the existence in the electrolyte of microheterogeneous nickel and cobalt compounds formed during alkalization of the near-cathode layer and their inclusion in the cathode precipitate together with dispersed ND particles introduced into the electrolyte from the outside.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…7H2O 8-15; C7H5NO3S 0,5-2,0; ND 0,5-2,5. Electrolysis modes: pH 1,5-5,0; temperature 20-60°C; cathode current density 0,5-43 A/dm 2 ; stirring with a mechanical stirrer at a speed of 80-120 rpm [17]. Kinetic studies [16][17] have shown the existence in the electrolyte of microheterogeneous nickel and cobalt compounds formed during alkalization of the near-cathode layer and their inclusion in the cathode precipitate together with dispersed ND particles introduced into the electrolyte from the outside.…”
Section: Methodsmentioning
confidence: 99%
“…The latter appear in electrolytes during their preparation, upon dissolution of anodes and / or as a result of alkalization of the near-cathode layer during a parallel reaction of hydrogen evolution. The presence of a dispersed phase in electrolytes-colloids combines them with electrolyte-suspensions for electrodeposition of CEC [17]. The result of the addition of the dispersed phase into electrolyte-colloids from the outside is а synergistic effect; it is expressed in the increased resistance of composite materials to friction and wear [18].…”
Section: Introductionmentioning
confidence: 99%
“…For research used electrolyte-colloid, composition (g/l): NiCl2 . 6H2O 200, H3BO3 30, NH4Cl 20, C7H5NO3S 1,0, Na2B10H10 (DHBN) 1,9; UDD 1,2; pH 3 [8], in the studies the concentration of additives and pH varied: DHBN 0-1.9; UDD 0-1.2; pH 1-3.…”
Section: Introductionmentioning
confidence: 99%
“…It should be understood that the electrodeposition of coatings with a dispersed phase in the composition occurs from electrolyte-suspensions obtained by the galvanic method and containing a dispersed phase introduced into the electrolyte, or electrolyte-colloids, in which the dispersed phase is formed during preparation or electrolysis [8][9]. Analysis of many experimental data [10][11][12] led to the conclusion that the process of formation of CEC consists of three main stages: 1) the supply of a particle to the cathode surface; 2) fixation (adsorption, adhesion) and 3) its overgrowth by precipitating metal.…”
Section: Introductionmentioning
confidence: 99%
“…There are several main directions for obtaining CECs, containing a dispersed phase [2][3][4]: coatings from electrolyte suspensions, obtained by a chemical or electrochemical method and containing a dispersed phase artificially introduced into the electrolyte; electrochemical coatings from electrolytes that form a dispersed phase during preparation or electrolysis (electrolytescolloids). Many studies are devoted to the study of the mechanisms of the formation of CEC in order to obtain their optimal exploitative characteristics [5,6].…”
Section: Introductionmentioning
confidence: 99%